Reconstruction of the centers affected by the 2009 earthquake - Contents and methods in the Reconstruction’s Plan development - Continenza, Romolo (DISEGNARECON, 2012)
The principle who guided the policy choices, in the reconstruction process of the damages caused by the earthquake of 2009, was to give priority to the reparation of buildings located outside the historic centres perimeter postponing its reparation to the approval of the Reconstruction plans. This choice was driven from the will to push ahead the more simple interventions implementation postponing the fate of historic centres to further investigations. The paper, as a result of experiences made in developing some reconstruction plans, highlights the cognitive issues needed in order to make this Urban Plan together with the significant differences in selecting its contents, imposed by the need to answer to the specific contextual situations. The case studies examined suggest, indeed, a range of choices ranging from the recovery the memory of a disappeared urban fabric, to the redesign of considerable portions of urban block until the recommendation of accurate restoration operations.